Bioaccumulation of trace metals in the coastal Borneo (Malaysia) and health risk assessment - Ramasamy, Nagarajan; Anandkumar, A.; Prabakaran, K.; Bing, C.; Rajaram, R.; Li, J.; Du, D. (2019)
The concentration of nine trace elements were analyzed in the different tissue organs of commonly available crabs (Portunus sanguinolentus, Portunus pelagicus and Scylla serrate) and bivalve (Polymesoda erosa) species collected from the Miri coast, Borneo in order to evaluate the potential health risk by consumption of these aquatic organisms. Among the analyzed organs, metal accumulation was higher in the gill tissues. The essential (Cu and Zn) and non-essential (Pb and Cd) elements showed the highest (i.e. Zn) and lowest concentrations (i.e. Cd) in their tissue organs, respectively. The estimated daily intake and hazard indices of all metals in the muscle indicate that the measured values were below the provisional tolerable daily intake suggested by the joint FAO/WHO Expert Committee on Food Additives. Compared to Malaysian and international seafood guideline values the results obtained from the present study are lower than the permissible limits and safe for consumption.